2018
DOI: 10.35957/jatisi.v4i2.99
|View full text |Cite
|
Sign up to set email alerts
|

Analisis End-User Computing Satisfaction (EUCS) Dan WebQual 4.0 Terhadap Kepuasan Pengguna

Abstract: World wide web merupakan salah satu aspek terpenting dari proses menghasilkan informasi yang ditujukan bagi masyarakat informasi. Banyaknya website yang berada pada domain ID .ac.id yang diperuntukkan bagi lembaga perguruan tinggi berfungsi sebagai media promosi dan peningkatan layanan mutu pendidikan. Tujuan penelitian ini adalah mengidentifikasi dan mengukur seberapa besar kontribusi End-User Computing Satisfation (EUCS) dan model WebQual 4.0 yang terdiri dari dimensi usability, information quality dan servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
1
0
6
Order By: Relevance
“…Penelitian tersebut bertujuan untuk mengidentifikasi kepuasan pengguna atas website Sekolah Tinggi ABC dengan model WebQual 4.0 dan EUCS. Hasil yang diperoleh dari penelitian tersebut menunjukkan bahwa EUCS dan WebQual 4.0 berpengaruh signifikan terhadap kepuasan pengguna [8]. Metode yang digunakan dalam penelitian tersebut mempunyai cara yang sama dengan penelitian ini, yaitu mengolah data dengan Structural Equation Modeling (SEM) dimana data yang diolah juga diperoleh dari responden melalui survei kuesioner.…”
Section: Kajian Pustakaunclassified
“…Penelitian tersebut bertujuan untuk mengidentifikasi kepuasan pengguna atas website Sekolah Tinggi ABC dengan model WebQual 4.0 dan EUCS. Hasil yang diperoleh dari penelitian tersebut menunjukkan bahwa EUCS dan WebQual 4.0 berpengaruh signifikan terhadap kepuasan pengguna [8]. Metode yang digunakan dalam penelitian tersebut mempunyai cara yang sama dengan penelitian ini, yaitu mengolah data dengan Structural Equation Modeling (SEM) dimana data yang diolah juga diperoleh dari responden melalui survei kuesioner.…”
Section: Kajian Pustakaunclassified
“…Penelitian sejenis yang menggunakan teknik pengolahan data berbeda (regresi linier dan IPA), diperoleh hasil yang bervariasi [10][11] [12]. Salah satunya menyatakan hanya dimensi usability dan service interaction yang berpengaruh signifikan terhadap kepuasan pengguna [13].…”
Section: Pendahuluanunclassified
“…The method used with a quantitative move toward, namely multiple linear weakening and showed that variables of usability and services interaction have a significant and positive effect on users approval [5], research that discusses developed a learning method is a mobile-based data structure where students can access materials, referral and applications interrelated to subject devoid of being limited by place and time, whenever and wherever. students arranged that application can optimize the learning process of data structure subject [6], research that discusses determine the quality of web conferencing so that students can enhance the learning process and to know the most significant indicator in the quality of e-Learning and dimensions of usability positive influence to user satisfaction [7], research that discusses the taking perspective of users about the information quality website and 95% self-confidence level is used and the result on the dimensions of information quality (usability quality, information quality, and service interaction quality) has significant influence against to user satisfaction [8], research that discusses the identify and measure involvement of End-User Computing Satisfaction (EUCS) and WebQual 4.0 model consist of usability, information quality and services interaction dimension to user satisfaction on ABC Institution website used quantitative move toward during structural equation modeling (SEM) analysis with assenting factor analysis technique [9], research that discusses the indicated that e-learning service quality was a second-order build comprise of three factors, namely, e-learning system quality, e-learning instructor and course materials quality, and elearning managerial and support service quality [10], research that discusses the evaluate e-learning websites based on the results of the WebQual questionnaire and calculations with the meaning-performance analysis method [11], research that discusses the found that level of significance and level of performance on the e-Questionnaire website that requests to be maximized in ease of use, appearance, and enhancement on the information and communication pages that must be measured by the manager of E-Questionnaire website [12], research that discusses the established IoT-Servqual model with four dimensions (i.e., Privacy, Functionality, Efficiency, and Tangibility) of many service quality models. These dimensions are essential and disposed towards the user leaning of IoT Services [13], research that discusses the quality of the website, such as Lazada.…”
Section: Related Workmentioning
confidence: 99%